Paesaggi Protetti Laboratori di sperimentazione per il paesaggio costiero euro-mediterraneo - Salizzoni, Emma (Premio Tesi di Dottorato, 2012)
The urgency for policies to plan and manage the European Mediterranean coastal landscape is now evident: along the Latin Arch exceptional landscape values are accompanied by a growing anthropic pressure that is speeding up its transformations, creating significant problems; it is here, more than in other places, that the challenge posed by the preservation-development pair emerges. This study looks at the strategies developed within three protected coastal landscapes that have taken up the challenge. Interpreted as test laboratories for landscape policies, they give precious cues for the planning and management of the ordinary coastal landscape.